Creation and Creativity in Medieval Art: Illustrating Genesis - Fricke, Beate (Amsterdam University Press, 2025)
Creation imagery in manuscripts made in the Middle Ages became a locus for visual experimentation as well as the expression of ideas about creativity. By examining representations of divine creation and illustrations of the creation stories in Genesis, this book links medieval ideas about creation, the characteristic of the Divine Creator, and the act of creation with themes in medieval thought about the work of medieval artists. Case studies from manuscripts illuminating the creation dating from the eleventh to the fourteenth century (Junius 11/The Cædmon Manuscript, Roda Bible & Ripoll Bible, Bible moralisées, Hamburg Bible, Holkhalm Bible) reveal self-reflective moments; where medieval artists relate artistic invention and theological debates about creation. This book traces the artists’ thinking in their own work and then contextualizes those visual cues within the context of philosophical arguments about the creation of the world. It also considers how Western medieval artists, in inventing original illuminations and experimenting with new representational modes, suggest potential analogies between their own work, God’s acts of creation, and nature’s generative force.